2012
DOI: 10.1007/s00464-012-2589-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized comparison of pain, inflammatory response, and short-term outcomes between single port and laparoscopic cholecystectomy

Abstract: Single-incision laparoscopic surgery does not significantly reduce systemic inflammatory response, postoperative pain, or analgesic use compared with LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 17 publications
4
43
1
2
Order By: Relevance
“…Several studies did not report on random sequence generation, allocation concealment or blinding, thereby making quality assessment a difficult task. High risk of bias was present in limited studies and regarded domains related to conflict of interest or funding sources [32,34,38], allocation concealment [17], attrition bias [17,25,27] and reporting bias [27].…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies did not report on random sequence generation, allocation concealment or blinding, thereby making quality assessment a difficult task. High risk of bias was present in limited studies and regarded domains related to conflict of interest or funding sources [32,34,38], allocation concealment [17], attrition bias [17,25,27] and reporting bias [27].…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 98%
“…Conversion was required in 6 patients of a single study, specifically 4 patients subjected to singleincision surgery with curved instruments and 2 conventional laparoscopic cholecystectomies [33]. Bile leak or subhepatic collection was reported in 5 studies [19,23,27,30,34], with an equal distribution among treatment arms (3 patients in each treatment group and 4 patients in the control group). The diagnosis was made through a drain tube in two studies which provided relevant information [27,34].…”
Section: Outcomes Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This applies to both gynecological and general surgical interventions [14,15,16]. Luna et al [17] compared single-incision surgery with conventional laparoscopy and found no difference in the CRP values. Most studies relate to gastrointestinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated in several studies 12,24,25 that IL-6 can be used as an inflammatory marker, since its levels are elevated early in the face of tissue damage. Therefore, the dosages of interleukin-6 and C-reactive protein have been used by several authors as a method of choice for the evaluation and comparison of the systemic inflammatory response in different groups 26,27 . Like IL-6, C-reactive protein can also be used as a marker of inflammation 2 .…”
Section: Sd: Standard Deviation; * Student T Test Comparison Of Meansmentioning
confidence: 99%